2020
DOI: 10.1021/acsomega.0c02068
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nitrofuran Metabolites in Fish by Ultraperformance Liquid Chromatography-Photodiode Array Detection with Thermostatic Ultrasound-Assisted Derivatization

Abstract: Nitrofuran (NF) is a class of broad-spectrum antibiotics that are used illegally in animal feeding. NF and its metabolites have proven to pose potential risk to human health. To address the current analytical needs to quantify low levels of NF metabolites in animal foods, a sensitive method was developed for simultaneous detection of four NF metabolites in fish products by an ultraperformance liquid chromatography-diode array detector (UPLC-DAD). With 2-nitrobenzaldehyde (2-NBA) as the derivatizing reagent, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 47 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…In this study, as NFZ was very unstable after entering an animal’s body, it could be quickly metabolized into SEM with smaller molecular weight in a short time and could consequently bind to tissue proteins in a relatively stable state. Because the molecular weight of SEM was too small, a derivatization reagent (2-NBA) was usually used to generate NPSEM, increasing its molecular weight [ 31 ]. For animal samples, the matrix component with the greatest interference in the extract was protein.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, as NFZ was very unstable after entering an animal’s body, it could be quickly metabolized into SEM with smaller molecular weight in a short time and could consequently bind to tissue proteins in a relatively stable state. Because the molecular weight of SEM was too small, a derivatization reagent (2-NBA) was usually used to generate NPSEM, increasing its molecular weight [ 31 ]. For animal samples, the matrix component with the greatest interference in the extract was protein.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicology research indicated that NFs and their metabolites are potentially hazardous substances, with possible carcinogenic, teratogenic, and mutagenic properties [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…9 So, therefore it is necessary to develop analytical tools which are capable of addressing this issue, and also an answer for this problem. In order to achieve this goal, researchers have used various analytical methods for the determination of NFT and 4-NP such as high performance liquid chromatography (HPLC), 10 colorimetry, 11 capillary zone electrophoresis, 12 spectroscopic determination, 13 liquid chromatography-mass spectroscopy (LC-MS), 14 flow injection analysis, 15 polarography 16 and electrochemical methods 17 were employed. The electrochemical method outperformed other methods due to its unique advantages such as rapidity, low limit of detection, no or easy sample pre-treatment, cost effectiveness, easy to operate, high sensitivity, high selectivity and portability.…”
Section: Introductionmentioning
confidence: 99%